Allergic Sensitization in Low-Income Urban Children: Relationship with Current Symptoms of Asthma and Rhinitis [Sensibilización Alérgica en Niños Urbanos de Escasos Recursos: Relación Con Síntomas Actuales de Asma y Rinitis] - Mallol-Villablanca, E; Raby-Amadori, P (Permanyer Publications, 2022)
Background: Recent information on the prevalence of allergic sensitization (AS) in children from low-income urban areas is limited. Methods: We conducted a cross-sectional, randomized, population-based study to determine the prevalence of AS, and its relationship with asthma and rhinitis in low-income schoolchildren in Santiago, Chile. The parents answered a standardized questionnaire on respiratory symptoms, and a skin prick test (SPT) for common aeroallergens was performed on all children. Results: In the 545 schoolchildren studied (mean age 8.3 ± 0.9 years), the prevalence of positive SPT was 25.5%. The current prevalence of asthma, rhinitis, and rhinoconjunctivitis was 20%, 43.4%, and 27.8%, respectively. SPT was positive in 30.6%, 32.8%, and 38.0% of children with current asthma, rhinitis, and rhinoconjunctivitis, respectively. Positive SPT was significantly associated with rhinitis and rhinoconjunctivitis (p < 0.001) but not with asthma. Breastfeeding for at least 4 months was significantly protective against AS (odds ratio [OR] 0.48, 95% confidence interval [CI] 0.26-0.78; p = 0.008); no other factor studied was associated with AS. Conclusions: The prevalence of AS was low; less than 40% of children with current asthma, rhinitis, or rhinoconjunctivitis symptoms evidenced AS. The prevalence of non-atopic asthma and rhinitis is consistent with previous findings in children from low-income urban areas. Other environmental factors, such as the high burden of respiratory infections and environmental pollution, might be more critical than atopy for developing asthma and rhinitis in schoolchildren from deprived urban areas. © 2022 Hospital Infantil de México Federico Gómez.